Postcolonial poetics : genre and form - Crowley, Patrick, 1964-; Hiddleston, Jane (Francophone postcolonial studies, 2011)
Postcolonial texts engage with the political world in a variety of ways, directly or indirectly, and it is in their specific uses of genre and form that they alter or develop our understanding of the particular contexts with which they grapple. This collection of essays on postcolonial poetics explores different kinds of literary writing, its blurring with other discourses and its manipulation of genre and form, in order to achieve a better understanding of its transformatory power. This study of the poetics of genre also sheds light on how different kinds of texts offer specific, distinct mod.